An evolutionary approach for solving the job shop scheduling problem in a service industry - Yousefi M.; Yousefi M.; Hooshyar D.; Oliveira J.A.S. (Universitas Ahmad Dahlan, 2023)
In this paper, an evolutionary-based approach based on the discrete particle swarm optimization (DPSO) algorithm is developed for finding the optimum schedule of a registration problem in a university. Minimizing the makespan, which is the total length of the schedule, in a real-world case study is considered as the target function. In order to clarify the problem and the proposed solution a small instance discusses then the problem with the real data is solved. Since the selected case study has the characteristics of job shop scheduling problem (JSSP), it is categorized as a NP-hard problem which makes it difficult to be solved by conventional mathematical approaches in relatively short computation time. 2015 International Journal of Advances in Intelligent Informatics. All rights reserved.